An In-Depth Morphological and Syntactic Analysis of the Poetic Language in The Snow-Storm by Ralph Waldo Emerson - Muhammad Haroon Jakhrani (Studies in Social Science & Humanities, 2023)
This research paper is a critical analysis of Ralph Waldo Emerson’s poem, The Snow-Storm. The paper examines the morphological and syntactic structure of the poem, analyzing its literary devices and themes. The analysis highlights the use of inversion, inflection, repetition, and metaphors in contributing to the poem’s central themes, such as the insignificance of humans in nature, the power of nature over humanity, and the constant flux of life. Additionally, this paper draws attention to the poem’s relevance to contemporary environmental issues, suggesting that the poem could reflect the importance of protecting and preserving nature. The limitations and scope of the research paper are also discussed. This research paper’s contribution to literary, social, and environmental studies is significant, as it illustrates literature’s interpretive possibilities in reflecting upon contemporary issues and human experiences.